Pengaruh Qanun Madrasah dan Keteladanan Guru terhadap Kedisiplinan Siswa Kelas VIII MTs Al Ma’had An-Nur Bantul - Lana Fauziyah; Lina; Muhammad Asrofi (QuranicEdu: Journal of Islamic Education, 2022)
This research aimed to (1) determine the relationship between madrasa qanuns and the discipline of class VIII MTs Al Ma'had An-Nur Sewon Bantul Yogyakarta, (2) find out the relationship between teacher exemplary and student discipline in the class, and (3) find out how much influence there is. madrasa qanuns and the teacher's example of student discipline in the class. This research used a quantitative method with three variables, namely the madrasa qanun variable (X1), teacher exemplary (X2), and student discipline (Y). The subjects in this research were students of class VIII who opened 80 people. Data was collected by using questionnaire, observation, documentation and interview methods. Based on the analysis conducted using multiple regression test with an error rate of 5%, it was concluded that: (1) there was a positive and significant relationship between the variables of Islamic qanun (X1) and student discipline (Y). It was indicated by the correlation value (r) of 0.739 and p (sig) of 0.000. (2) there was a positive and significant relationship between the teacher exemplary variable (X2) and student discipline (Y). It was indicated by the correlation value (r) 0.291 and p (sig) of 0.000. (3) together the variables of madrasa qanun (X1) and teacher's example (X2) affect student discipline by 56.2%.